The role of β-titanium ligaments in the deformation of dual phase titanium alloys - Jun,T-S; Maeder,X; Bhowmik,A; Guillonneau,G; Michler,J; Giuliani,F; Britton,TB (Materials Science and Engineering: A, 2019)
Multiphase titanium alloys are critical materials in high value engineeringcomponents, for instance in aero engines. Microstructural complexity isexploited through interface engineering during mechanical processing to realisesignificant improvements in fatigue and fracture resistance and strength. Inthis work, we explore the role of select interfaces using in-situmicromechanical testing with concurrent observations from high angularresolution electron backscatter diffraction (HR-EBSD). Our results aresupported with post mortem transmission electron microscopy (TEM). Usingmicro-pillar compression, we performed in-depth analysis of the role of selectβ-titanium (body centred cubic) ligaments which separate neighbouringα-titanium (hexagonal close packed) regions and inhibit the dislocationmotion and impact strength during mechanical deformation. These results shedlight on the strengthening mechanisms and those that can lead to strainlocalisation during fatigue and failure.